Discourse - from the theoretical and methodological perspective - Urszula Ostrowska (University of Lower Silesia, 2014)
Undertaking the issues addressed in this article was influenced by at least a couple of reasons, among which especially the fact of spreading the concept of discourse in various spheres of social life, despite the vague, imprecise meaning of the term, the sense of which usually emerges from the context in which it is used. Moreover, what seems interesting is the broad enough discretion in the use of the category of discourse by the authors of papers of various problem scope and level and singling out different types of discourse in the considerations undertaken (i.e., political, legal, historical, philosophical, educational, scientific, etc.) without clear criteria of this typology. What is more, the issue of qualitative research on discourse, which is still not adequately appreciated, not only in the sciences of education, also appears to be important. I begin my considerations with a few introductory remarks, and then refer to the more important etymological issues, and consider the question of importance of discourse. Furthermore, I pay attention to the emerging problems with the concept of discourse and refer to some selected aspects of discourse research, including the role and position of the researcher. Finally, I attempt to summarize the discussion.